Answer :
To solve the equation [tex]\(\sin (3x + 9)^\circ = \cos (5x - 7)^\circ\)[/tex], we can use the trigonometric identity that connects sine and cosine:
[tex]\[ \sin \theta = \cos (90^\circ - \theta) \][/tex]
Applying this identity, we can rewrite [tex]\(\cos (5x - 7)^\circ\)[/tex] as:
[tex]\[ \cos (5x - 7)^\circ = \sin \left(90^\circ - (5x - 7)^\circ\right) \][/tex]
So our original equation becomes:
[tex]\[ \sin (3x + 9)^\circ = \sin \left(90^\circ - (5x - 7)^\circ\right) \][/tex]
Simplify the argument of the sine function on the right-hand side:
[tex]\[ 90^\circ - (5x - 7)^\circ = 90^\circ - 5x + 7 = (97^\circ - 5x) \][/tex]
Now the equation is:
[tex]\[ \sin (3x + 9)^\circ = \sin (97^\circ - 5x) \][/tex]
Since the sine function is periodic and its values are equal when the angles differ by multiples of [tex]\(360^\circ\)[/tex] or are identical, we can equate the angles (since we are dealing with small angles in degrees, we can ignore the multiples of [tex]\(360^\circ\)[/tex]):
[tex]\[ 3x + 9 = 97 - 5x \][/tex]
To find [tex]\(x\)[/tex], we solve this equation step-by-step:
1. Add [tex]\(5x\)[/tex] to both sides:
[tex]\[ 3x + 5x + 9 = 97 \][/tex]
2. Simplify the left-hand side:
[tex]\[ 8x + 9 = 97 \][/tex]
3. Subtract 9 from both sides:
[tex]\[ 8x = 97 - 9 \][/tex]
4. Simplify the right-hand side:
[tex]\[ 8x = 88 \][/tex]
5. Finally, divide both sides by 8:
[tex]\[ x = \frac{88}{8} \][/tex]
[tex]\[ x = 11 \][/tex]
Therefore, the value of [tex]\(x\)[/tex] is:
[tex]\[ \boxed{11} \][/tex]
[tex]\[ \sin \theta = \cos (90^\circ - \theta) \][/tex]
Applying this identity, we can rewrite [tex]\(\cos (5x - 7)^\circ\)[/tex] as:
[tex]\[ \cos (5x - 7)^\circ = \sin \left(90^\circ - (5x - 7)^\circ\right) \][/tex]
So our original equation becomes:
[tex]\[ \sin (3x + 9)^\circ = \sin \left(90^\circ - (5x - 7)^\circ\right) \][/tex]
Simplify the argument of the sine function on the right-hand side:
[tex]\[ 90^\circ - (5x - 7)^\circ = 90^\circ - 5x + 7 = (97^\circ - 5x) \][/tex]
Now the equation is:
[tex]\[ \sin (3x + 9)^\circ = \sin (97^\circ - 5x) \][/tex]
Since the sine function is periodic and its values are equal when the angles differ by multiples of [tex]\(360^\circ\)[/tex] or are identical, we can equate the angles (since we are dealing with small angles in degrees, we can ignore the multiples of [tex]\(360^\circ\)[/tex]):
[tex]\[ 3x + 9 = 97 - 5x \][/tex]
To find [tex]\(x\)[/tex], we solve this equation step-by-step:
1. Add [tex]\(5x\)[/tex] to both sides:
[tex]\[ 3x + 5x + 9 = 97 \][/tex]
2. Simplify the left-hand side:
[tex]\[ 8x + 9 = 97 \][/tex]
3. Subtract 9 from both sides:
[tex]\[ 8x = 97 - 9 \][/tex]
4. Simplify the right-hand side:
[tex]\[ 8x = 88 \][/tex]
5. Finally, divide both sides by 8:
[tex]\[ x = \frac{88}{8} \][/tex]
[tex]\[ x = 11 \][/tex]
Therefore, the value of [tex]\(x\)[/tex] is:
[tex]\[ \boxed{11} \][/tex]